Meaning Of The Word 'Perish' According To 2 Corinthians 2:7 - Robert Tri Zebua (Theological Journal Kerugma, 2022)
The research approach in this journal uses a theological approach, specifically based on 2 Corinthians 2:7. If it is specified again, regarding the biblical texts that are considered to contain elements of Perish. Emphasis of research it tends to use a biblical theology approach. The biblical approach intends to expose the selected text. Systematics Doctrine does not get a large space or portion in this study. The results of this study can be used as the basis for the material about the word Perish in learning media or further application of learning media. Besides that, it also becomes an added value for knowledge of terms in the Bible for readers.